Actress Felicità von Vestvali and her role of a travesty on stage and in life (1828-1880). Part I - Keller Andrei Victorovich (Studia Humanitatis)
The article examines the milestones of the life of an opera singer and dramatic actress Anna Marie Stagemann, known under the pseudonym Felicità von Vestvali (1828-1880). The study rediscovers the name of the famous travesty, performer of the male roles of Hamlet, Romeo, Petruchio and Uriel Acosta, on the stages of European and American opera and drama theatres. The beginning of her career as an opera singer was marked by a debut, which was a resounding success, at the La Scala theatre in Milan in 1853. The year 1863 was a turning point as, during an unsuccessful tour in New York, the singer decided to pursue a career as a dramatic actress. Having made her debut in New York, like before, as a travesty playing Romeo in 1864, she brought back the success and reverence of the former admirers of her talent. Vestvali continued to play Hamlet on the stages of Europe after becoming the first woman to perform this role in the USA.